1992
DOI: 10.1152/ajprenal.1992.263.3.f363
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization and release of angiotensin and renin in renal cortical cells

Abstract: Angiotensin is generated within the kidney, but the precise loci for the formation of angiotensin I (ANG I) and angiotensin II (ANG II) have not been demonstrated. We performed electron microscopy immunocytochemistry in kidney sections of 10-day-old (newborn) and adult Wistar-Kyoto (WKY) rats using specific antibodies to renin, ANG I, ANG II, and angiotensinogen (AO). Renin, ANG I, ANG II, and AO were present in juxtaglomerular (JG) cells. Renin was largely confined to cytoplasmic granules; ANG I and ANG II we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 0 publications
0
42
0
Order By: Relevance
“…Cells were cultured for 48 h on Permanox plastic-coated multi-well chamber slides (Nunc, Inc., Naperville, IL). Immunoperoxidase staining was performed using the avidin-biotin peroxidase complex (ABC) kit from Vector Laboratories, Inc. (Burlingame, CA), as described previously (10,11). Cells were fixed in methanol (4 Њ C) for 10 min, followed by a 10-s exposure to acetone (4 Њ C), and then air dried.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cultured for 48 h on Permanox plastic-coated multi-well chamber slides (Nunc, Inc., Naperville, IL). Immunoperoxidase staining was performed using the avidin-biotin peroxidase complex (ABC) kit from Vector Laboratories, Inc. (Burlingame, CA), as described previously (10,11). Cells were fixed in methanol (4 Њ C) for 10 min, followed by a 10-s exposure to acetone (4 Њ C), and then air dried.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, local RAS components or tissue generation of Ang II have been detected in several organs such as brain (Phillips et al 1993, Sernia 1995, pituitary (Thomas & Sernia 1990a), adrenal glands (Vinson 1995, Mulrow & Franco-Saenz 1996, heart (Dostal 2000), kidneys (Celio 1981, Hunt et al 1992, Darby & Sernia 1995, gonads (Thomas & Sernia 1990b, Vinson et al 1997) and pancreas (Leung et al 1998, 1999, Tahmasebi et al 1999, Leung & Carlsson 2001). The role played by these tissue RAS is not well understood and they have been proposed to regulate local blood flow or to fulfil specific functions according to the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…32,33,53 In contrast to vascular smooth muscle cells, proximal [57][58][59][60] Immunohistochemical studies using antibodies to angiotensinogen have clearly localised angiotensinogen to the proximal tubule segment. 56,61 These results indicate that much of the intrarenally-produced angiotensinogen is derived from proximal tubule cells and suggest it is one source of the intratubular concentrations of Ang I and Ang II. It has been noted that the preponderance of immunoreactive angiotensinogen in proximal tubule cells is located along the luminal membrane of the proximal tubule cells thus supporting the notion that angiotensinogen could be secreted into the tubular lumen and/or producing its metabolites intracellularly and secreting them directly into the tubule lumen.…”
Section: Origins Of Intrarenal Angiotensin IImentioning
confidence: 88%
“…Studies utilising immunohistochemical techniques demonstrated that Ang I and Ang II are co-localised with renin in JGA cells and vascular smooth muscle cells of the afferent arteriole. [53][54][55][56] These studies suggested that Ang II could be formed or internalised into the smooth muscle cells. 32 Because there is no direct evidence for intracellular angiotensinogen in vascular smooth muscle cells, it is more likely that Ang I and/or Ang II are internalised via receptor-mediated endocytosis in smooth muscle cells.…”
Section: Origins Of Intrarenal Angiotensin IImentioning
confidence: 95%
See 1 more Smart Citation